Dietary iron intake, serum ferritin and haemoglobin levels, and cognitive development scores of infants aged 6–8 months (Medical Journal of Indonesia, 2011)
Background: Iron deficiency during infancy may lead to negative effect on cognitive function and psychomotor development. This study aimed to investigate serum ferritin, haemoglobin level and its relation to cognitive development score in infants aged 6-8 months. Methods: This cross-sectional study was done on 76 infants recruited from several selected community health center in Kampung Melayu Village, Jatinegara Jakarta who had fulfilled the study criteria. Data collected consist of age, weight, height, head circumference, energy, protein and iron intake, serum feritin levels, haemoglobin levels and cognitive development score using Capute Scales method (Cognitive Adaptive Test/ Clinical Linguistic Auditory Milestone Scales/ CAT-CLAMS). Results: Among 74 infants aged 6-8 months, 73% had less dietary iron intake as compared to its RDA (7 mg/d), 18.9% were with serum ferritin less than normal value (20 μg/L), and 56.7% with haemoglobin levels less than normal value (11 mg/dL). In relation to cognitive development score, this study revealed that the CAT score was signifi cantly lower among subjects with hemoglobin value less than 11 mg/dL (p = 0.026). Conclusion: Early prevention of impaired cognitive development is urgently needed by providing iron-rich complementary foods to infants since 6 months (mo) old to maintain the normal level of hemoglobin. (Med J Indones 2011; 20:46-9) Keywords: cognitive score, ferritin, hemoglobin, infants